2017
DOI: 10.1001/jamaoto.2017.1686
|View full text |Cite
|
Sign up to set email alerts
|

Association of Krouse Classification for Sinonasal Inverted Papilloma With Recurrence

Abstract: Inverted papillomas classified as stage T3 according to the Krouse classification system presented a 51% higher likelihood of recurrence. Head and neck surgeons must be aware of this higher likelihood of recurrence when planning and performing surgery for sinonasal inverted papilloma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 30 publications
(86 reference statements)
3
33
1
6
Order By: Relevance
“…Demographic risk factors cited in the literature include smoking history and prior sinonasal surgery . Cited paraclinical risk factors include tumor location assessed via nasal endoscopy and/or CT scan, tumor stage, dysplasia, human papilloma virus status, and surgical technique . Assessment of clinical and comorbidity risk factors, however, has not been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Demographic risk factors cited in the literature include smoking history and prior sinonasal surgery . Cited paraclinical risk factors include tumor location assessed via nasal endoscopy and/or CT scan, tumor stage, dysplasia, human papilloma virus status, and surgical technique . Assessment of clinical and comorbidity risk factors, however, has not been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Some observational studies have shown significant differences in recurrence rate among Krouse and Cannady stages, whereas other studies have found no such association between any classification system and recurrence . Furthermore, a meta‐analysis revealed an increased risk of recurrence between Krouse T2 and T3 stages (OR 1.51, 95% CI 1.09–2.09) but no difference between T1 and T2 and between T3 and T4 . One reason for a lack of association is the heterogeneity of certain stages, including Krouse T3/Cannady T2 and Krouse T4.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations